Transformasi Operasional LPD: Peran Pelatihan Komputer dan Manajemen Pemasaran pada Karyawan dalam Meningkatkan Pelayanan: Pengabdian - Ida Ayu Nyoman Yuliastuti; I Gusti Agung Ayu Istri Lestari; Komang Dean Ananda; Made Agung Raharja (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this community service activity is to improve the quality of administrative management, improve marketing management and services provided by LPD employees. The implementation method includes socialization regarding the importance of business management and marketing, technical training on the use of computer applications such as Microsoft Excel and Word, direct practice in financial recording and management of LPD customer data. The results of the activity showed an increase in employee skills as indicated by an increase in the ability to prepare financial reports using Microsoft Excel more quickly, neatly, and accurately, as well as the implementation of digital-based marketing strategies through social media Instagram which has been proven to expand the reach of services, especially in reaching the younger generation around Sembung Gede Village. Administrative efficiency has increased significantly because the use of computer applications can speed up work processes and strengthen transparency, thereby increasing public trust in LPD. Strengthening the capacity of LPD employees through computer training and marketing management assistance not only improves the internal performance of LPDs, but also has an impact on the sustainability of the socio-economic function of traditional institutions in building village economic independence.